Deciphering the Epigenetic Alphabet Involved in Transgenerational Stress Memory in Crops - Mladenov, Velimir; Fotopoulos, Vasileios; Kaiserli, Eirini; Karalija, Erna; Maury, Stephane; Baranek, Miroslav; Segal, Naama; Testillano, Pilar S; Vassileva, Valya; Pinto, Glória; Nagel, Manuela; Hoenicka, Hans; et al. (My University, 2021)
Although epigenetic modifications have been intensely investigated over the last decade due to their role in crop adaptation to rapid climate change, it is unclear which epigenetic changes are heritable and therefore transmitted to their progeny. The identification of epigenetic marks that are transmitted to the next generations is of primary importance for their use in breeding and for the development of new cultivars with a broad-spectrum of tolerance/resistance to abiotic and biotic stresses. In this review, we discuss general aspects of plant responses to environmental stresses and provide an overview of recent findings on the role of transgenerational epigenetic modifications in crops. In addition, we take the opportunity to describe the aims of EPI-CATCH, an international COST action consortium composed by researchers from 28 countries. The aim of this COST action launched in 2020 is: (1) to define standardized pipelines and methods used in the study of epigenetic mechanisms in plants, (2) update, share, and exchange findings in epigenetic responses to environmental stresses in plants, (3) develop new concepts and frontiers in plant epigenetics and epigenomics, (4) enhance dissemination, communication, and transfer of knowledge in plant epigenetics and epigenomics.
Keywords: Abiotic stress; Biotic stress; Epigenetic; Methodology; Stress memory; Transgenerational memory